A new early Miocene astrapotheriid (Mammalia, Astrapotheria) from Northern Patagonia, Argentina - Kramarz, Alejandro Gustavo (2011)
In this contribution we describe the astrapotheriid Comahuetherium coccaorum gen. nov. sp. nov. from Colhuehuapian (early Miocene) sediments of the Cerro Bandera Formation in Neuquén Province, Northern Patagonia, Argentina, also recorded in levels of equivalent age at the Gran Barranca south of Lake Colhué Huapi, in Chubut Province, central Patagonia, Argentina. Comahuetherium coccaorum is a small species with generalized astrapotheriid characters, but it shows some derived dental features (i.e. absence of P3, straight upper canines, and lingual cingulum enclosing the central valley on M3), which were preliminarily interpreted as indicating affinities with the uruguaytheriine astrapotheres. However, the result of a phylogenetic analysis indicates that the new taxon is part of the stem group of the clade formed by Uruguaytheriinae plus Astrapotheriinae, and that the abovementioned dental specializations were acquired independently, an evolutionary pattern not previously reported among these mammals. The body mass estimations for Comahuetherium and other late Oligocene - Miocene astrapotheriids reveal a wide range of body size, suggesting that these mammals played diverse ecological roles.